THE ANALYSIS ON HYBRID SUPERCONDUCTING FAULT CURRENT LIMITER (SFCL) USAGE TO LIMIT SHORT CIRCUIT FAULT CURRENT OF 20 KV ELECTRIC POWER DISTRIBUTION IN SENGKALING SUBSTATION - Eko Nurcahyo; Bambang Prio Hartono; Choirul Saleh (Merdeka Malang University, 2020)
Abstract—The occurrence of fault in electrical power system operation is inevitable. The causes of fault in electrical power transmission and distribution system for instances are lighting strikes on transmission canal, tree collapses, or short circuit inter-phases to the ground. In order to protect the equipment and the whole electrical system in Sengkaling Substation and to reduce the short circuit fault current quickly within timeframe of ½ cycle, it requires Superconducting Fault Current Limiter (SFCL) which is going to be placed on the bus that comes close to a critical point. The designing and analysis on the system of before and after hybrid SCFL installment utilize PSCAD software. The simulation result obtained by installing hybrid SFCL in incoming bus 2 (20 kV) was that hybrid SFCL was able to reduce short circuit fault current in ½ initial cycle with L-G fault of 16.77 kA changed to 5.9 kA, L-L-G fault of 35.38 kA changed to 9.15 kA, L-L-L-G fault of 38.36 kA changed to 9.8 kA, and L-L fault of 28.89 kA changed to 4.35 kA. The average percentage of short circuit fault current that was reduced by hybrid SFCL was 74.12%.